1997
DOI: 10.1271/bbb.61.1133
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Food Microorganisms by High-pressure Carbon Dioxide Treatment with or without Explosive Decompression

Abstract: In order to elucidate the sterilization mechanism underlying the explosive decompression system, baker's yeast was pressurized with COz, NzO, N z , or Ar gas at 40atm and 40°C for 4h, and then explosively discharged. The survival ratio was markedly decreased only by the treatments with COz and NzO, which are relatively soluble gases in water, suggesting that the microorganisms' death may be highly correlated with gas absorption by the cells. Lower decompression rates to atmospheric pressure, however, led to ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
39
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(43 citation statements)
references
References 8 publications
2
39
0
Order By: Relevance
“…Although numerous reports have demonstrated that carbonation at moderate temperature (20 − 40℃) can inactivate microorganisms in their vegetative form, this is not sufficient for substantial reductions in viable spore counts (Garcia-Gonzalez et al, 2007). Enomoto et al (1997) also reported that carbonation at temperatures above 50℃ significantly inactivated bacterial spores. The elucidation of the mechanisms for this enhanced inactivation of spores under heating may lead to more effective use of carbonation in the control of bacterial spores.…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous reports have demonstrated that carbonation at moderate temperature (20 − 40℃) can inactivate microorganisms in their vegetative form, this is not sufficient for substantial reductions in viable spore counts (Garcia-Gonzalez et al, 2007). Enomoto et al (1997) also reported that carbonation at temperatures above 50℃ significantly inactivated bacterial spores. The elucidation of the mechanisms for this enhanced inactivation of spores under heating may lead to more effective use of carbonation in the control of bacterial spores.…”
Section: Introductionmentioning
confidence: 99%
“…A number of mechanisms have been proposed to explain high-pressure CO 2 sterilization, including cell membrane rupture caused by the increase in internal pressure combined with rapid pressure release (17,18) and the extraction of lipids from the cell membrane (19). Equally, scCO 2 diffusion into the cell and the resultant changes in the cellular environment, such as a decrease in pH, could be lethal (17).…”
mentioning
confidence: 99%
“…At moderate temperatures and pressures, CO 2 treatment significantly inactivates bacterial vegetative cells, whereas pressure treatment alone has little effect (19,30). There have been some previous studies of inactivation of bacterial spores by CO 2 treatment (1,4,5,16,18); for example, CO 2 treatment can substantially inactivate bacterial spores at temperatures above 50°C. Another study showed that Geobacillus stearothermophilus spores were poorly inactivated by CO 2 treatment at 35°C and 20 MPa (18).…”
mentioning
confidence: 99%